KEMAMPUAN BAKTERI ENDOFIT TANAMAN SEMANGKA DALAM MENEKAN PERKEMBANGAN PENYAKIT BERCAK DAUN YANG DISEBABKAN OLEH JAMUR COLLETOTRICHUM SP. - Eryna Elfasari Rangkuti; Dwi Suryanto .; Kiki Nurtjahja .; Erman Munir . (Universitas Lampung, 2014)
Ability of watermelon endophytic bacteria to suppress development of leaf spot disease caused by Colletotrichum sp. A studi on assay of endophytic bacteria to control Colletotrichum sp., causal agent of leaf spot disease on watermelon, was conducted. Colletotrichum sp. was isolated from infected leaf of leaf spot disease, while endophytic bacteria were isolated from stem, leaf, and root of watermelon healthy plant. Antagonistic assay was conducted by dual culture method. Hyphal abnormalities as a result of antagonistic assay was observed using light microscope. To determine the ability of endophytic bacterial isolates to control leaf spot disease, watermelon seeds were treated by dipping the seed in endophytic bacterial suspension. Seven endophytic bacterial isolates showed to inhibit Colletotrichum sp. to some extent. Two isolates DS 01 and BS 01 showed relatively high inhibition zone compared to others, therefore were choosen for further study. Abnormal hyphae such as broken, lysis, twisted, curled, and swollen hyphae were recorded as the result of antagonistic assay. Watermelon seed treatment revealed that dipping the seed in endophytic bacterial suspension of DS 01 and BS 01 reduced leaf spot disease to 12 and 24%, but inhibited seed growth by 12% and 44%, respectively. It seemed that all treatments showed to reduce seedling performance i.e seedling height, leaf number, and dry weight, compared to that of (-) control. DS 01 however seemed to increase dry weight of watermelon plants.